Flower identification using fuzzy expert system / Mohd Amiruddin Awi - Awi, Mohd Amiruddin (2006)
Nowadays, people like to do everything within the computer. With this technology, help many people in doing their job easier and faster or even cheaper. In identifying the flower name, many of us use manually by finding the flower in books because difficult to find any system that can help people in identify the flower. For the solution, this prototype is being developed. A Flower Identification using Fuzzy Expert System is a web-based prototype developed to identify and recognize the flower name and extra information. This prototype recognizes the flower from the input data from user. The valuable input data includes color of flower petals, number of petals and calculation on one flower petal. The prototype process the input and identify the flower have similarity with the input. The final results from prototype are flower image and information about that flower. At the end of the development, project objectives accomplished. The project should be developed using fuzzy logic expert system. The prototype output which is flower image is same as the unknown flower image. The methods used are fuzzy logic for the color determination and expert system. As a conclusion, this prototype achieved the objectives and succeed in doing their task for identify the unknown flower.